\(\dfrac{12}{17}+\left(\dfrac{-6}{19}\right)+\dfrac{5}{17}+\left(\dfrac{-13}{19}\right)-\dfrac{1}{2}=\left(\dfrac{12}{17}+\dfrac{5}{17}\right)+\left(\dfrac{-6}{19}+\dfrac{-13}{19}\right)-\dfrac{1}{2}=1+\left(-1\right)-\dfrac{1}{2}=0-\dfrac{1}{2}=-\dfrac{1}{2}\)
` 12/17 + ( -6/19) + 5/17 + ( -13/19 ) -1/2 = ( 12/17 + 5/7 ) + ( -6/16 + -13/19) - 1/2 = 1 + ( -1) -1/2 = 0 - 1/2 = -1/2 `
\(=\left(\dfrac{5}{17}+\dfrac{12}{17}\right)+\left(\dfrac{-13}{19}+\dfrac{-6}{19}\right)-\dfrac{1}{2}=\dfrac{17}{17}+\left(-\dfrac{19}{19}\right)-\dfrac{1}{2}\)
\(=1+\left(-1\right)-\dfrac{1}{2}=-\dfrac{1}{2}\)